Signature of Triaxially Precessing Magnetars in Gamma-Ray Burst X-Ray Afterglows - Biao Zhang; Shu-Qing Zhong; Long Li; Zi-Gao Dai (The Astrophysical Journal)
The X-ray afterglows of some gamma-ray bursts (GRBs) exhibit plateaus, which can be explained by the internal dissipation of a newborn millisecond magnetar wind. In the early phase of these newborn magnetars, the magnetic inclination angle undergoes periodic changes due to precession, leading to periodic modulation of the injection luminosity due to magnetic dipole radiation. This may result in quasiperiodic oscillations on the plateaus. In this paper, we identify four GRBs with regular flux variations on their X-ray afterglow plateaus from Swift/X-Ray Telescope data before 2023 November, three of which exhibit periodicity. Based on the likelihood of supporting a precessing magnetar as the central engine, we classify them into three categories: Gold (GRB 060202 and GRB 180620A), Silver (GRB 050730), and Bronze (GRB 210610A). We invoke a model of magnetic dipole radiation emitted by a triaxially freely precessing magnetar whose spindown is dominated by electromagnetic radiation, to fit the light curves. Our model successfully reproduces the light curves of these four GRBs, including the regular flux variations on the plateaus and their periodicity (if present). Our work provides further evidence for early precession in newborn millisecond magnetars in GRBs.